The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23105780
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Treatment Protects Auditory Hair Cells from Cisplatin-Induced Cell Death Accompanied by Upregulation of LMO4

Abstract: Ototoxicity is one of the main dose-limiting side effects of cisplatin chemotherapy and impairs the quality of life of tumor patients dramatically. Since there is currently no established standard therapy targeting hearing loss in cisplatin treatment, the aim of this study was to investigate the effect of nimodipine and its role in cell survival in cisplatin-associated hearing cell damage. To determine the cytotoxic effect, the cell death rate was measured using undifferentiated and differentiated UB/OC−1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Future studies will have to demonstrate if nimodipine has the potential to become such a drug. Although beneficial effects of nimodipine have been shown on remyelination both in vivo [ 20 , 21 ] and in vitro, in addition to the effects on astrocytes, microglia, and neurons [ 20 , 22 , 23 , 25 , 84 ], these effects could not be explained by a VGCC-dependent mode of action in all cases [ 22 , 25 , 84 ]. Therefore, further investigation is necessary to identify potential interaction partners of nimodipine at a cellular level, which would clarify its role and potential in (re-) myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will have to demonstrate if nimodipine has the potential to become such a drug. Although beneficial effects of nimodipine have been shown on remyelination both in vivo [ 20 , 21 ] and in vitro, in addition to the effects on astrocytes, microglia, and neurons [ 20 , 22 , 23 , 25 , 84 ], these effects could not be explained by a VGCC-dependent mode of action in all cases [ 22 , 25 , 84 ]. Therefore, further investigation is necessary to identify potential interaction partners of nimodipine at a cellular level, which would clarify its role and potential in (re-) myelination.…”
Section: Discussionmentioning
confidence: 99%
“…5,7-Dihydroxy-4-methylcoumarin (D4M) markedly regulated p-c-Jun N-terminal kinase (p-JNK) and elevated the expression ratio of p-FoxO1/FoxO1, thus attenuating SGNs injury, mitochondrial dysfunction, ROS accumulation and cisplatin-induced caspase-dependent apoptosis ( Li et al, 2023 ). As a calcium channel antagonist with lipophilic properties, nimodipine pre-treatment could significantly reduce cisplatin-induced apoptosis via regulating LIM domain only 4 (LMO4) levels and activating associated Akt, cAMP-response element binding protein (CREB), and Signal transducer and activator of transcription 3 (Stat3) protein levels ( Fritzsche et al, 2022 ; Table 3 ).…”
Section: Protective Measures Against Cisplatin Ototoxicitymentioning
confidence: 99%
“…Many different drugs and natural products reduce cisplatin toxicity [ 3 , 5 ]. A recent study showed that nimodipine pre-treatment of auditory cells decreases cisplatin-induced cell death in vitro [ 6 ]. Cisplatin-based chemotherapy increases the formation of reactive oxygen and nitrogen species, triggering oxidative modification of cochlear proteins and leading to the downregulation of the otoprotective transcription regulator LIM Domain Only 4 (LMO4) [ 7 ].…”
mentioning
confidence: 99%
“…Cisplatin-based chemotherapy increases the formation of reactive oxygen and nitrogen species, triggering oxidative modification of cochlear proteins and leading to the downregulation of the otoprotective transcription regulator LIM Domain Only 4 (LMO4) [ 7 ]. Nimodipine pre-treatment upregulates LMO4 and ultimately activates antiapoptotic pathways, reducing cisplatin ototoxicity [ 6 ]. In addition, emerging research has demonstrated the importance of treatment formulation beyond the treatment itself to prevent/reduce cisplatin toxicity.…”
mentioning
confidence: 99%